2016
DOI: 10.1175/jcli-d-15-0580.1
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Climate Variability on Extreme Ocean Surface Wave Heights Assessed from ERA-Interim and ERA-20C

Abstract: Extreme ocean surface wave heights significantly affect coastal structures and offshore activities and impact many vulnerable populations of low-lying islands. Therefore, better understanding of ocean wave height variability plays an important role in potentially reducing risk in such regions. In this study, global impacts of natural climate variability such as El Niño–Southern Oscillation (ENSO), North Atlantic Oscillation (NAO), and Pacific decadal oscillation (PDO) on extreme significant wave height (SWH) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
67
0
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 74 publications
(78 citation statements)
references
References 59 publications
(81 reference statements)
10
67
0
1
Order By: Relevance
“…This method was further refined by Wang and Swail (2001). The iterative-based MK method has been shown to be efficient in detecting trends, especially in extreme meteorological time series data (Kumar et al, 2016). In this study, we adopted the iterative-based MK method detailed in Wang and Swail (2001) to detect trends in extreme precipitation.…”
Section: Mann-kendall Trendmentioning
confidence: 99%
“…This method was further refined by Wang and Swail (2001). The iterative-based MK method has been shown to be efficient in detecting trends, especially in extreme meteorological time series data (Kumar et al, 2016). In this study, we adopted the iterative-based MK method detailed in Wang and Swail (2001) to detect trends in extreme precipitation.…”
Section: Mann-kendall Trendmentioning
confidence: 99%
“…Studies based on satellite altimeter [Izaguirre et al, 2011] and reanalysis data [Dodet et al, 2010;Plomaritis et al, 2015;Kumar et al, 2016] revealed strong relationships between wind-wave climate and large-scale teleconnection patterns, such as the Antarctic Oscillation (AAO), the El Niño-Southern Oscillation (ENSO), and the North Atlantic Oscillation (NAO). Some of these indices are expected to intensify under increased anthropogenic forcing [Zheng et al, 2013;Cai et al, 2014], but it is not well understood how wind-wave variability and especially extreme waves will relate to these climate indices in a warmer world.…”
Section: Introductionmentioning
confidence: 99%
“…With the availability of the global reanalysis dataset from European Centre for Medium-Range Weather Forecasts Re-Analysis-Interim (ERA-I; Dee et al, 2011), now it is possible to study the long-term changes in different atmospheric and ocean parameters. Several researchers (e.g., Harley et al, 2010;Hemer et al, 2010;Kumar et al, 2016) across the globe has used ERA-I datasets to examine the interannual wave climate variability. Previous studies along the eastern Arabian sea (Kumar & Naseef, 2015;Shanas & Sanil Kumar, 2014b, 2014c suggest that ERA-I datasets give a good agreement with the measured data.…”
Section: Introductionmentioning
confidence: 99%
“…Several researchers studied interannual variability of wave climate and their response to wellknown climate indices (e.g, Hemer et al, 2010;Izaguirre et al, 2011;Splinter et al, 2012). For coastal and ocean engineering applications, the relationship between wave climate variability and teleconnection patterns along the Atlantic, Pacific, and the Indian Ocean were discussed by many (Izaguirre et al, 2011(Izaguirre et al, , 2010Kumar et al, 2016;Semedo et al, 2011;Shimura et al, 2013). Earlier studies have shown that on interannual time scales, the Pacific Ocean variability modulates Indian Ocean (Du et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation